Islamic Fashion And Religiosity Towards Fashion Consumption - Shaleha, Waode Maratun; Kolewora, Riez Kifli (FASTABIQ: JURNAL STUDI ISLAM, 2025)
This study aims to analyze the influence of fashion motivation and religiosity on fashion consumption, with fashion consciousness as a mediating variable. The population of this study consists of female students from the Faculty of Islamic Economics and Business (FEBI) at Muhammadiyah University. The sample size is 72 respondents. The data collection instrument used is a questionnaire distributed directly to respondents, and the data analysis method employed is the Structural Equation Model (SEM). The results indicate that fashion motivation has a positive and significant effect on fashion consciousness, fashion motivation has a positive and significant effect on fashion consumption, and fashion consciousness has a positive and significant effect on fashion consumption. Moreover, fashion motivation positively and significantly influences consumption through fashion consciousness as a mediating variable. On the other hand, religiosity does not have a positive or significant effect on fashion consciousness, fashion consumption, or fashion consumption through fashion consciousness as a mediating variable. The limitations of this study are as follows: the research uses only four variables, namely fashion motivation, religiosity, fashion consciousness, and fashion consumption. Additionally, the data collection technique solely relies on online questionnaire distribution, making it impossible for the researcher to monitor the respondents during the questionnaire completion process directly. Lastly, the study is confined to the Faculty of Islamic Economics and Business at Muhammadiyah University.Keywords: Fashion Consciousness; Fashion consumption; Motivation fashion; Religiosity